Optimization of Operating Condition for the Production of Edible Film from Cuttlefish’s Bone Gelatin as Instant Noodle Seasoning Packaging (Universitas Negeri Semarang, 2022)
Edible film is a thin layer commonly used to coat food, which is biodegradable and can be consumed. The functions of edible film such as an inhibitor of mass transfer, oxygen, aroma and other dissolved substances. Cuttlefish bones contain protein which can be processed into gelatin and applied as edible film. This study aims to determine the quality and optimal operating conditions of edible films. The research method that used in this research is descriptive quantitative method. The experimental design in this study used a factorial design with independent variables including: gelatin concentration (6 and 8%), glycerol concentration (10% and 20%) and pectin concentration (0.5 and 10%). In this study, the ranged of water vapor transmission rate (wvtr) from eight sample are 9.716 - 11.725 g/m2.day, the best result of water vapor transmission rate analysis shown at operating conditions of 8% gelatin concentration, 20% glycerol concentration and 1% chitosan concentration which was 9.716 g/m2.day. In this research the higher gelatin concentration causes an increase in the value of water vapor transmission rate, while the higher the concentration of glycerol causes an increase in the value of wvtr, thickness, elongation but decreases the value of tensile strength an solubility, the higher chitosan concentration causes an decreases in the value of wvtr, tensile strength, elongation, solubility but increase the value of thickness The best results from the thickness, solubility, tensile strength, elongation tests were 0.22 mm; respectively; 1 minute 17 seconds; 6.30 MPa; 166.5%. The morphological analysis using SEM analysis shows that the surface of the molecular structure of the edible film looks smooth, uneven and slightly porous.